HUBUNGAN KEAKTIFAN BERTANYA DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI MADRASAH IBTIDAIYAH DARUL FALAH SELAKAU - Hadri; Dina Anika Marhayani; Rika Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine whether or not there is a relationship between active questioning and students' mathematics learning outcomes. This research method is correlation/relationship research with a quantitative approach. The population in this study were all fourth grade students at Madrasah Ibtidaiyah Darul Falah Selakau. The sampling technique in this research is Purposive Sampling. The sample in this research was class IV students at Madrasah Ibtidaiyah Darul Falah Selakau, totaling 30 students.  Data was obtained through mathematics learning outcomes test instruments and student questioning activity questionnaires. The materials used in the mathematics learning outcomes test are rectangles and squares. The data analysis technique used is Pearson product moment correlation. The results of the research show that: 1) The activeness of asking questions by fourth grade students at Madrasah Ibtidaiyah Darul Falah Selakau is relatively high, based on the calculation of student scores with an overall average of 67. 2) Students' mathematics learning outcomes in rectangles and squares are relatively high with an average overall 71.5. 3) There is a relationship between students' activeness in asking questions and students' mathematics learning outcomes with a correlation coefficient (r) of 0.7 in the strong or high category and a coefficient of determination of 49%. So from the results of the research that has been carried out it can be concluded that there is a relationship between active questioning and students' mathematics learning outcomes in rectangular and square material.